Pilot location selection for cargomatics: contactless parcel pick-up points - TUNCALI YAMAN, TUTKU (My University, 2022)
As of 2022, even though the effect of the pandemic reduced, we pursued to gain new habits in our lives. E-commerce companies, which we also made purchases with before the pandemic, have now become indispensable for many people, especially those living in big cities. The increasing volume of e-commerce and delivering intensified packages to consumers during the pandemic period have also brought new ideas. With the participation of modern smart technologies in these developments, various opportunities have begun to show themselves from the point of view of entrepreneurs and enterprises. One of the creative ideas in question is parcel pick-up points (Cargomatic). In our research, a pilot study was conducted on the selection of relevant locations of the Cargomatics, which will be located at many points in the future Aiming to demonstrate a case study for the location selection out of 5 candidate districts within the borders of Istanbul by using one of the novel fuzzy techniques a hybrid of spherical fuzzy AHP and TOPSIS. Evaluations regarding the criteria importance were made by high-level managers with experience in the cargo industry and criteria weights were provided via the Spherical Fuzzy AHP method, and with the help of TOPSIS, Kadikoy, Umraniye, and Atasehir are ranked as the 3 most suitable districts for the use of Cargomatics.
Keywords: BİLGİSAYAR BİLİMİ, YAPAY ZEKA; Bilgisayar Bilimi; Mühendislik, Bilişim ve Teknoloji (ENG); BİLGİSAYAR BİLİMİ, İNTERDİSİPLİNER UYGULAMALAR; COMPUTER SCIENCE, ARTIFICIAL INTELLIGENCE; COMPUTER SCIENCE; Engineering, Computing & Technology (ENG); COMPUTER SCIENCE, INTERDISCIPLINARY APPLICATIONS; Parcel Pick-up points; Spherical fuzzy AHP; TOPSIS